Workshop Pencucian Luka Kaki Diabetik Menggunakan Bahan Alam bagi Perawat di Puskesmas Mapane, Kabupaten Poso, Provinsi Sulawesi Tengah - Dafrosia Darmi Manggasa; Dewi Nurviana Suharto; Supirno Supirno (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Wound care of diabetic foot ulcer by Public Health Center nurses still use povidone iodine and rivanol which are toxic to tissues. Innovations in wound care including the use of natural materials have been proven to be effective in accelerating the healing of diabetic foot ulcers. This community service activity aims to increase the knowledge and skills of Public Health Center nurses in wound care using natural materials. The implementation method, namely workshops and wound care practices using natural materials, was held for 1 day on July 11 2022 at the Mapane Health Center. The target was Public Health Center nurses, totaling 28 participant. The form of evaluation is measuring the knowledge and skills of nurses before and after the activity. The results showed that the participants knowledge increased from 60.7% to 89.3% and the average skill score increased from 9.04 to 16.14. The conclusion is that after the workshop activities there was an increase in the knowledge and skills of Public Health Center nurses for wound care using natural materials. Suggestions for Public Health Center nurses to be able to utilize natural materials in the diabetic foot wound care.